HUBUNGAN FREKUENSI DAN LAMA MENYUSU DENGAN PERUBAHAN BERAT BADAN NEONATUS DI WILAYAH KERJA PUSKESMAS GANDUSARI KABUPATEN TRENGGALEK - Trio Linda Familia Endra Rini; Siti Rahayu Nadhiroh (Media Gizi Indonesia, 2015)
Breast milk is the ideal source of nutrition with a balanced composition of both quantity and quality, also adjusted to needs of the baby in the growth stage. Babies are considered get enough breastmilk if they achieve significant weight gain. The purpose of this research is to find the relationship between frequency and duration of breastfeeding with neonatal weight changes in Gandusari Trenggalek Public Health Center. This study is an observational analytic with cross sectional design. Sample in this study was a neonatal in Gandusari Trenggalek Public Health Center. The study was conducted in April-Juni 2015 by number of samples as much as 32 neonatus. The statistic test using chi-square with 95% confident interval. Most of neonatus got frequencies of breastfeeding in “often” category (84.4%), duration of breastfeeding in “enough” category (78.1%), and the majority of neonatal infant have a weight change in the “up“ category (53.1%). Based on statistical analysis, there was a relationship between the frequency of breastfeeding with the neonatal weight changes (p=0.015) and there was no relationship between the duration of breastfeeding with the neonatal weight changes (p=0.209). The conclusion of this research is that neonatus weight change associated to frequency of breastfeeding, but not related to duration of breastfeeding. The importance to communicate the information and education of breastfeeding to mothers about the practice of breastfeeding frequency within 24 hours so that ut can optimize baby’s growth.Keywords: duration of breastfeeding, frequency of breastfeeding, neonatal infant, weight changes